DIPO PURE, ALAT PEMURNI AIR SEBAGAI SOLUSI PENANGANAN AIR ROB - Heydar, Roqy; Sofyan, Mudzofar; Muslihudin, Mohammad; Putri, Prafitra Asih Rahmawati Sinar; Suhandono, Steven (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Currently, the effort to overcome the tidal water disaster is merely raising the ground level which tend to be difficult and ineffective. The solution is done by using the water as drinking water with the help of water purifier. The purpose of this program is to characterize tidal water, prototyping tools, and characterize the resulting water. This water purifier is designed to use three kinds of macro filter namely silica sand, activated carbon, zeolite, and the membranes Reverse Osmosis. In addition, the tool is equipped with a photocatalyst that functions to neutralize organic compounds. Reverse Osmosis Membrane equipped with backflush process to extend the life of the membrane. Tidal water test results in Laboratory of PDAM TirtaMoedal shows some parameters that exceed drinking water quality standard, dissolved solids is 1848 mg/lt of quality standard of 500 mg/l, levels of Chloride is 1692 mg/l of quality standard of 250 mg/l, Ammonia levels is 1.28 mg/l of quality standard of 1.5 mg/l, levels of Manganese is 0.522 mg/l of quality standard of 0.1 mg/l. Then the results of lab tests show that the water output of this tool is potable, itâsindicated by dissolved solids was reduced to 10 mg/l, Chloride level is 5.98 mg/l, Ammonia level is 0.1 mg/l and Manganese level is 0,006 mg/l. Thus, it can be concluded this water purifier is capable of purifying water rob into potable water.Keywords: Tidal water, rob water, water purifier, reverse osmosis, potable water